RECONSTRUCTION OF LOVE WAVE GROUP VELOCITY MAP OF THEÃâÃâZÃâÃâ GEOTHERMAL FIELD USING SEISMIC AMBIENT NOISE - WAHIDA (NIM: 12313032), ARZALIA
The “Z”geothermal field is located approximately 35 km south of Bandung, West Java. It is one of the biggest geothermal field in Indonesia and exploration process in this area still on going. The high cost of exploration and exploitation become the main obstacle in the development of geothermal energy. Therefore, this research use ambient noise tomography method which can reduce the development cost. This method use seismicnoise near the geothermal field without any active source neither from earthquake nor explosion. The objective of this research is to characterize Love wave group velocity to reconstructgroup velocity maps.Data come from three months (January-March 2015) recording data of twelve seismometer array which located near the research area. Love wave were obtained from rotation of two horizontal components (N-S and E-W) with rotation angle is azimuth between two stations. Cross correlation process use to calculateGreen’s Function. Then dispersion curveextracted using Frequency Time Analysis method with Multiple Filtering Technique. The set of dispersion curves are then use to create group velocity maps for period 2s, 2.5s, 3s, 3.5s, and 4s. Generally, from group velocity maps, shows a relatively higher velocity zone at the south of Mt. Puncak Besar and this high velocity zone increase for the higher period. On the other hand, a zone with relatively lower velocity emerge at the east of Mt. Gambung and at the north-west of Mt. Wayang and this low velocity zone become decrease with increasing period.